DETEKSI FRAUD: QUO VADIS SISTEM PENGENDALIAN INTERNAL PEMERINTAH - Taufiqur Rohman; Hamidah Hamidah (Behavioral Accounting Journal, 2019)
This study discusses about how the Government's Internal Supervisory Apparatus understands its role in fraud detection and the Government's Internal Control System. The aim of this study is to find out the extent to which the Government's Internal Supervisory Apparatus understands their role in fraud detection according to the Government's Internal Control System in the Provincial Government "XYZ". This research is a descriptive qualitative study. The results showed that APIP's understanding was very diverse and many of them did not understand their role in fraud detection and prevention. It is also similar with the Government's Internal Control System associated with the APIP role. The condition that becomes the common thread is not yet the functioning of the early warning system for efforts to eradicate corruption in this country.